2021
DOI: 10.18697/ajfand.98.19370
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to dietary guidelines among Type 2 Diabetes Mellitus patients at Moi Teaching and Referral Hospital-Kenya

Abstract: Diabetes is one of the major non-communicable diseases and an important public health problem not only in Kenya but all over the world. It is estimated that the prevalence of diabetes in Kenya is at 5% among adults. Although the care regimen is complex, patients with good diabetes self-care behaviors can attain excellent glycemic control. It is vital that patients adhere to their stipulated routines to minimize the burden of the disease on the healthcare systems. The objective of this study was to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The socio-demographic characteristics with a non-significant association with knowledge were age, education and occupational status. This echoes findings from an earlier Kenyan study by [110]. However, other studies have shown a significant association between these characteristics and knowledge [111], [107], [112].…”
Section: Associations Between Various Variablessupporting
confidence: 86%
“…The socio-demographic characteristics with a non-significant association with knowledge were age, education and occupational status. This echoes findings from an earlier Kenyan study by [110]. However, other studies have shown a significant association between these characteristics and knowledge [111], [107], [112].…”
Section: Associations Between Various Variablessupporting
confidence: 86%